A Non-Canonical MITE in the WOX11 Promoter Is Associated with Robust Crown Root development in Rice. (21st June 2022) - Zhang, Ting; Xiang, Yimeng; Geng, Leping; Jiang, Wei; Cheng, Saifeng; Zhao, Yu
Abstract: The formation of tissues and organs in multicellular organisms is tightly controlled by transcriptional programs determined by temporal and spatial patterns of gene expression. As an important regulator of rice crown root development, WOX11 is essential for crown root formation and its transcript level is positively correlated with crown root biomass. However, how WOX11 is regulated during crown root primordium emergence and outgrowth still remains unknown. In this study, variations of the WOX11 genomic sequence were analyzed, and the highest genetic diversity was found within its promoter, which contained a non-canonical miniature inverted-repeat transposable element (ncMITE) sequence. Analysis of the WOX11 promoter-driven reporter gene GUS ( β-glucuronidase ) transgenic plants pWOX11 ( ncMITE + ): GUS and pWOX11 ( ncMITE − ): GUS uncovered higher GUS expression levels in crown roots of pWOX11 ( ncMITE + ): GUS plants. Furthermore, pWOX11 ( ncMITE + ): WOX11-FLAG in wox11 background could complement the crown root number and length compared to those of the wild type, while pWOX11 ( ncMITE − ): WOX11-FLAG could not. These results suggested that the ncMITE was positively associated with WOX11 transcripts in rice crown roots. In addition, DNA methylation nearby the ncMITE region attenuated the activation effect of the ncMITE on WOX11 expression, which might also be the cause conferred to the root-specific expression of WOX11 . This work provides novel insight into WOX11 expression regulation and reveals a promising target for genetic improvement of root architecture in rice.